Sistem Informasi Gereja Berbasis Web Pada GPIBK Jemaat Betel Sambulangan - Heriyanto Sahidu; Riswandi Kinait (Jurnal Ilmiah Sistem Manajemen Informatika dan Komputerisasi Akuntansi, 2022)
The problem encountered during this research was that records such as congregation lists, organizational structures, and lists of church activities still used the manual method with book media, so that when the information was needed it took longer to find it as well. Financial recording is also done manually by the church treasurer, who is still using Microsoft Excel in the manufacturing process. The research method used is descriptive method. The data collection methods are observation methods, interview methods and library methods. The observation method is direct observation. The interview method is to ask questions to informants about the problems encountered, while the library method is to collect data from several reference books related to the problem of writing this paper. The results of this research are in database design with ERD and system design with DFD in building information systems, resulting in Information Systems. In conclusion, with the construction of a Web-Based Church Information System at the GPIBK Congregation of Bethel Sammbulangan, it is hoped that it can help and simplify and streamline time in carrying out the data management process